CeraMIXlife (Korea Ceramic Foundation, 2011)
Exhibition held April 29-July 17, 2001 at the Yeoju World Ceramic Livingware Gallery and September 24-November 22, 2011 at the Yeoju Bandal Art Museum during the 6th Gyeonggi International CeraMIX Biennale, 2011.